A cultura organizacional da coamo e os seus canais de comunicação com os cooperados. - Rodrigues, Adriana Barbosa (Universidade Federal do Tocantins, 2023)
This work aims to present the communication mix of the COAMO cooperative and its organizational culture. The cooperative is located in Campo Mourão in the state of Paraná and has 29,000 associated farmers and 7,000 employees. The text was developed in the form of a thematic seminar based on the book 40 years of Coamo de Eloy Olnto, bibliographic research on the cooperative's website. It is these representations of set of beliefs and cooperative values that make it different from other market companies that operate in the same branch, even though the cooperative is a company located in the interior of Paraná, given that there are excellent success cases of companies and industries that seek large centers to and develop. Thus, it is perceived that the cooperative culture is responsible for shaping the identity of an organization and all its associates and collaborators in favor of common goals.